Cover Feature: [(Me6TREN)MgOCHPh2][B(C6F5)4]: A Model Complex to Explore the Catalytic Activity of Magnesium Alkoxides in Ketone Hydroboration (Eur. J. Inorg. Chem. 45/2021). Issue 45 (9th November 2021) - Ankur,; Kannan, Ramkumar; Chambenahalli, Raju; Banerjee, Sumanta; Yang, Yan; Maron, Laurent; Venugopal, Ajay
Abstract : The Cover Feature shows a concerted carbonyl hydroboration mechanism involving Mg−O, B−H, and C=O bonds. Homoleptic magnesium alkoxides catalyze ketone hydroboration with a turn‐over frequency (TOF) reaching up to 59, 400 h −1 and exhibit exceptional functional group tolerance. This TOF is so far the best observed in a main group catalyst without the involvement of a metal hydride intermediate. The newly proposed mechanism finds general applicability in magnesium alkoxides and stimulates interest in exploring other metal alkoxides in reduction chemistry. More information can be found in the Full Paper by L. Maron, A. Venugopal and co‐workers .